EXPRESSING THE LINGUISTIC LANDSCAPE OF THE WORLD THROUGH IDIOMS IN ENGLISH LITERATURE AND UZBEK LITERATURE - Izentaeva Rayhona Nokisbaevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article describes in detail the expression of the linguistic landscape of the world in English and Uzbek languages through idioms, the parallel occurrence of lexical and phraseological meanings, the study of national and cultural characteristics of idioms of English and Uzbek languages.